Miss Mary's money : fortune and misfortune in a North Carolina plantation family, 1760-1924 - Jones, H. G. (Houston Gwynne), 1924-2018; Southern, David, 1946-2021 (McFarland & Company, Inc., Publishers, 2014)
"The Smith fortune was made by Mary's grandfather, Revolutionary War veteran Francis Jones, and survived the profligacy of his son-in-law, Dr. James Smith, before being willed to the university and the North Carolina Episcopal diocese. Hundreds of descendants have been virtually ignored. This book, the result of eight years of research, is for them"--